2019
DOI: 10.1111/imm.13097
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell activation by transgenic rice seeds expressing the genetically modified Japanese cedar pollen allergens

Abstract: Summary Transgenic rice seeds that contain genetically modified Cry j 1 and Cry j 2, the two major allergens of Cryptomeria japonica (Japanese cedar; JC), have been developed as immunotherapeutic candidates for JC pollinosis. Because the transgenic rice (TG‐rice) seeds express allergens containing whole amino acid sequences of Cry j 1 and Cry j 2 in the endosperm tissue (edible part of rice grain), they can potentially target all Cry j 1‐ and Cry j 2‐specific T‐cells. However, it was unknown whether antigenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We verified antigenicity of Tg-rice seeds to T-cells through the analysis of the proliferative responses of T-cells in Cry j 1-or Cry j 2immunized mice or T-cell lines to Tg-rice seed extract. [1] Furthermore, we evaluated basophil activation caused by Tg-rice seeds in patients with JC pollinosis. [2] However, the antigenicity and safety of Tg-rice seeds had not been verified concurrently in patients with JC pollinosis.…”
mentioning
confidence: 99%
“…We verified antigenicity of Tg-rice seeds to T-cells through the analysis of the proliferative responses of T-cells in Cry j 1-or Cry j 2immunized mice or T-cell lines to Tg-rice seed extract. [1] Furthermore, we evaluated basophil activation caused by Tg-rice seeds in patients with JC pollinosis. [2] However, the antigenicity and safety of Tg-rice seeds had not been verified concurrently in patients with JC pollinosis.…”
mentioning
confidence: 99%
“…The most common allergen responsible for allergic rhinitis in Japan is Japanese cedar ( Cryptomeria japonica ) pollinosis, [11]. Takaishi et al [12, 13] recently developed transgenic rice that expresses all possible T-cell epitope repertoires of Cry j 1 and Cry j 2, the molecular determinants of Japanese cedar. They showed that allergen-sensitized mice that ate transgenic rice daily for 3 weeks had a marked suppression of allergen-specific CD4+ T-cell proliferation, IgE and IgG levels compared with mice fed non-transgenic rice, in response to challenge with crude C. japonica pollen allergen.…”
mentioning
confidence: 99%